Equity lost: Sweden and Finland in the struggle for PISA scores. (May 2023) - Muench, Richard; Wieczorek, Oliver; Dressler, Julian
This study seeks to explore the effect of tools of school governance advanced by the global reform agenda (1) on student performance and (2) on reducing the effect of sociodemographic variables on this performance. To do so, we compare two Nordic welfare states with an egalitarian tradition: Sweden and Finland. The Swedish school system has undergone comprehensive market-based and accountability-driven reforms beginning in the early 1990s. The Finnish school system is still based on the professional trusteeship of teachers, but has moderately implemented reforms of decentralization, enhancing school autonomy and opportunities of school or curriculum choice beginning in the late 1990s. Our analysis comprises of two steps. In the first step, a literature review of the reforms and their effects in Sweden and Finland is carried out. In the second step, regression analyses are conducted using data from the OECD's Programme for International Student Assessment (PISA) of 2000, 2009, and 2015. The results show an increasing influence of sociodemographic factors and growing inequality and no effect of governance tools as recommended by the global reform agenda in both countries over time, but more so and earlier in Sweden than in Finland.